OPTIMASI USAHA PERIKANAN MINI PURSE SEINE DI KABUPATEN JENEPONTO PROVINSI SULAWESI SELATAN (Optimization of Mini Purse Seine Fishery in Jeneponto District, South Sulawesi Province) - Mukhlisa A. Ghaffar; Sugeng H. Wisudo; Iin Solihin (Buletin PSP, 2007)
The small pelagic in Jeneponto is highly potential, but since 2001-2004 years there are degradation indication of haul activity wich marked by degradation of mini purse seine number. The objectives of the research are: 1) to estimate the level of MEY exploiting of small pelagis becoming target of mini purse seine, and 2) to determine production factors which is playing a part in improvement of productivity of mini purse seine. The production surplus method, Gordon Schaefer model and multiple regression analysis were used in this study. The result from bio-economic analysis showed that at actual condition have come near optimum level for exploiting of small pelagic. The optimum catch of small pelagic is 3.783.376,09 kilo grams per year with standard effort of 8.723 trip per year. Specially far mini purse seine, optimum effort is 47% from standard effort or equivalent by 26 unit of gears. Production factors that give signifiront effect to fish production of mini purse seine are machine strength, mini purse seine length and number of lamp.Keywords: optomization, mini purse seine, bio-economic